HUBUNGAN KETERPAPARAN PORNOGRAFI DI INTERNET DENGAN SIKAP BERPACARAN REMAJA PADA KELAS XI DI SMK NU 02 ROWOSARI KABUPATEN KENDAL - Budi Astyandini; Khobibah Khobibah; Ma’rifatul Laely (Midwifery Care Journal, 2020)
Teenagers often experience problems related to sexuality or reproductive health. A lot of information through the means of the print, electronic broadcast is vulgar and not educational, but more likely to influence and encourage irresponsible sexual behavior. The design of this study uses analytic surveys with cross sectional approaches. The population is class XI students, amounting to 225 students. The research sample of 70 respondents. The sampling technique uses simple random sampling. The type of analysis used is univariate, bivariate and Chi Square test. The research instrument used a questionnaire that was previously tested for validity and reliability. The results of this study showed that most students were exposed to pornography on the internet with a total of 48 students (68.6%). And positive teen dating attitudes 58 students (82.9%). From the results of this study, the p value was 0.013 0.05. This study concluded that there was a relationship between pornography exposure on the internet and the attitude of adolescent dating in class XI at SMK NU 02 Rowosari. It is expected that adolescents should increase knowledge about reproductive health and enhance positive activities. The teachers put more emphasis on moral education so that students avoid the negative effects of exposure to electronic or internet facilities that deviate and avoid the negative effects of bad dating behavior.